2X-7X+6=0 equação do segundo grau
Soluções para a tarefa
Respondido por
0
Vamos lá
A= 2
B= -7
C = 6
Δ = b² - 4 • a • c
Δ = (-7 )² - 4 • 2 • 6
Δ = 49 - 48
Δ = 1
X = ( -b ± √ Δ ) / 2 • a
X = ( 7 ± √ 1 ) / 2 • 2
X = ( 7 ± 1 ) / 4
X1 = 7 + 1 / 4 = 6 / 4 = 1, 5
X2 = 7 - 1 / 4 = 8 / 4 = 2
S { 1, 5 ; 2 }
A= 2
B= -7
C = 6
Δ = b² - 4 • a • c
Δ = (-7 )² - 4 • 2 • 6
Δ = 49 - 48
Δ = 1
X = ( -b ± √ Δ ) / 2 • a
X = ( 7 ± √ 1 ) / 2 • 2
X = ( 7 ± 1 ) / 4
X1 = 7 + 1 / 4 = 6 / 4 = 1, 5
X2 = 7 - 1 / 4 = 8 / 4 = 2
S { 1, 5 ; 2 }
Perguntas interessantes
Inglês,
10 meses atrás
Matemática,
10 meses atrás
Matemática,
10 meses atrás
Matemática,
1 ano atrás
Artes,
1 ano atrás
Administração,
1 ano atrás
Matemática,
1 ano atrás